Reward and Job Satisfaction: An Evidence from Private Colleges of Nepal (OCEM Journal of Management, Technology & Social Sciences, 2023)
Human resources are the pivot of organizational effectiveness and the most significant asset an organization can hold. Retaining a skilful and well-equipped workforce in an organization is pertinent to an institution's growth and overall performance. Satisfied employees certainly contribute to the organization's competitive advantage over its competitors. The present study investigates the relationship between employees' rewards and job satisfaction in Nepalese private colleges. The instrument used in information gathering was a structured questionnaire.The study employed a descriptive survey design in gathering data from 400 members of the teaching and non-teaching staff at private colleges. The data were analyzed using percentages, means, and correlation. The results indicate a positive correlation (r = .460) between the reward system and satisfaction. It demonstrates that if there is a change in the reward system by a point, it will bring a change in satisfaction by .460 points. The implications of this study would be beneficial for college educators, young researchers, education leaders, administrators, private college investors, and college teachers to understand the current teachers' retention intention.